Rancang Bangun Media Pembelajaran Matematika Berbantuan Educandy - Abdul Karim; Indah Mayang Purnama; Yogi Wiratomo; Fauzi Mulyatna (ARITHMETIC: Academic Journal of Math, 2022)
The purpose of this development research is to design mathematics learning media with the help of educandy applications for grade II elementary school teachers. The place of this research will be carried out at the Mathematics Laboratory of Indraprasta University PGRI with a research time of five months. The type of research used is the type of research and development (Research and Development). This research procedure adapts the ADDIE Model (Analysis, Design, Development, Implementation, Evaluate). The subjects in this study were educational games mathematics learning media using the educandy application on elementary school class II questions. The results of the research on the design of this mathematics learning media have been arranged questions in the form of educational games for grade II elementary schools. Educational game contains questions on whole numbers from 0-1000, addition and subtraction, multiplication and division.